2010
DOI: 10.1007/s00586-010-1343-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical advantages of dual over single iliac screws in lumbo-iliac fixation construct

Abstract: The development of iliac screws has provided a markedly easier way for spino-pelvic instrumentation than the classical Galveston technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 16 publications
4
44
0
1
Order By: Relevance
“…22 Our results show that both interbody fusions with cages and use of a rod with sublaminar hooks decrease the incidence of failures. These satisfactory results are attributable to the fact that both interbody cages and rods with compression hooks reduce the significant flexion stresses produced on the rods in the lumbosacral spine.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…22 Our results show that both interbody fusions with cages and use of a rod with sublaminar hooks decrease the incidence of failures. These satisfactory results are attributable to the fact that both interbody cages and rods with compression hooks reduce the significant flexion stresses produced on the rods in the lumbosacral spine.…”
Section: Discussionmentioning
confidence: 54%
“…19,21,22 In a previous study that presents incidence of implant failures similar to ours, 14 the incidence of failures of implants using one or two bilateral iliac screws for long fusions in patients with scoliosis of neurological etiology was evaluated, determining that the use of two bilateral iliac screws significantly reduced the number of instrumentation failures. These results do not match those of our study, in which similar percentages of complications were presented using one, two, or more iliac screws.…”
Section: Discussionmentioning
confidence: 79%
“…However, the use of iliac screws with long length and thick diameter could be an issue in young patients with thick iliac cortex width. The virtual screws used in the current study are long and have large diameters and may not be smaller than clinically utilised screws in most patients [16,17]. The current pass ratio of iliac screws with 100 mm length and 10 mm diameter is about 75 % in a small entry point zone, and the pass ratio of shorter screws with 80 mm length and same diameter is greater than 90 % within the same entry zone.…”
Section: Discussionmentioning
confidence: 85%
“…In terms of the biomechanical properties, the dual iliac screw was stiffer in compression and torsion than the single screw [17]. To have two iliac screws in one side, the first screw should be located more distally in the current entry zone.…”
Section: Discussionmentioning
confidence: 98%
“…the two screws can be placed into the same -lower -or into two different -upper and lower -iliac columns). 25 Further modification of SPF was published as four rod (FRR) or double-rod double iliac screw (DDS) reconstruction technique (Figure 2/D). [26][27][28][29] The biomechanical analyses showed that the additional lumbopelvic rods could increase the rigidity of the construct.…”
Section: Reconstruction Of the Biomechanicsmentioning
confidence: 99%